2015
DOI: 10.1017/s1368980015000324
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic differences in predictors of frequent dairy food consumption among Australian adolescents: a longitudinal study

Abstract: Objective: Sufficient dairy food consumption during adolescence is necessary for preventing disease. While socio-economically disadvantaged adolescents tend to consume few dairy foods, some eat quantities more in line with dietary recommendations despite socio-economic challenges. Socio-economic variations in factors supportive of adolescents' frequent dairy consumption remain unexplored. The present study aimed to identify cross-sectional and longitudinal associations between intrapersonal, social and environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(97 reference statements)
1
1
0
Order By: Relevance
“…That HRQoL becomes lower in females than males after the age of 12 and before the age of 13 years implies that this would be a suitable point at which to target intervention. Also as expected, given previous research [1,3,16,[20][21][22] there were gender differences in dietary patterns. Together, the observed variation in diet and HRQoL justify analysing the relationship between dietary patterns and HRQoL separately in males and females.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…That HRQoL becomes lower in females than males after the age of 12 and before the age of 13 years implies that this would be a suitable point at which to target intervention. Also as expected, given previous research [1,3,16,[20][21][22] there were gender differences in dietary patterns. Together, the observed variation in diet and HRQoL justify analysing the relationship between dietary patterns and HRQoL separately in males and females.…”
Section: Discussionsupporting
confidence: 89%
“…A longitudinal study conducted in Norway observed a decrease in HRQoL (Kidscreen10) in both boys and girls aged 11-14 years over three years [19]. Compared to females, adolescent males make less healthy food choices [1,3,16,[20][21][22]51] and consume meat more frequently [20,[23][24].. Given some evidence for gender differences in HRQoL along with consistent evidence for gender differences in dietary practices, boys and girls have been considered separately for the purpose of this analysis.…”
Section: Introductionmentioning
confidence: 99%